The place of azithromycin in the treatment of infectious diseases in children - S.A. Kramarоv; L.V. Zakordonets (Aktualʹnaâ Infektologiâ, 2020)
Azithromycin remains one of the most prescribed antibiotics in the world for the treatment of infections of the respiratory system, gastrointestinal tract, urogenital system and skin. In recent years, there has been an increase in antibiotic-resistant strains among pathogens of infectious diseases. Azithromycin compares favorably with most antibiotics by its multifaceted action, which, in addition to antimicrobial activity, includes anti-inflammatory and immunomodulating effects that ensures high clinical efficacy of the drug in the treatment of acute and chronic infections. The article presents data of international recommendations for the treatment of infectious diarrhea of various etiologies, Lyme disease, pertussis. Azithromycin is recommended as the drug of choice for empirical and selective therapy of major bacterial intestinal infections in children, for the etiotropic treatment of pertussis, Lyme disease.